Empowering Kelompok Perempuan Pesisir Indonesia (Kppi) To Modify Moringa Leaf Fish Balls To Overcome Stunting In Bagan Deli Village - Syarifah; Wahyuni, Arlinda Sari; Pujiati; Lubis, Zulhaida; Chairunny, Cici; Nabila, Salsa; Pohan, Indah Zakia (Universitas Negeri Medan, 2025)
Stunting is a condition in which children experience impaired growth, so that their height is notappropriate for their age due to chronic nutritional problems. In Bagan Deli urban village, Medan Belawan subdistrict, stunting in children under five is a public health problem. The proportion of stunted children in BaganDeli Village is 10.37%, and children with poor nutrition (below the red line) is 2.9%. The service activity wascarried out on Friday, July 26, 2024 in Bagan Deli Village with participants as many as 10 members of theIndonesian Coastal Women's Group (KPPI) partners and 10 pregnant women and mothers who have toddlers. Thepurpose of the service activity is to increase participants' understanding and knowledge, especially related tostunting and skills in processing moringa leaf meatballs made from fish. The service method was carried out byconducting socialization / training on stunting and cooking demonstrations as well as pre-test and post-test tomeasure participants' understanding and knowledge before and after the material was delivered. The resultsshowed an increase in knowledge before and after the training. Of the 20 training participants, the average increasein respondents' knowledge was 1.7, which showed that this increase was statistically significant.